2005
DOI: 10.1164/rccm.200505-686oc
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Alveolar Macrophage Activation State Induced by Cigarette Smoking

Abstract: Rationale: Macrophages are believed to play a central role in emphysema based largely on data from mouse models. However, the relevance of these models to smoking-related lung disease in humans is uncertain. Objectives: We sought to comprehensively characterize the effects of smoking on gene expression in human alveolar macrophages and to compare these with effects seen in transgenic mouse models of emphysema. Methods: We used DNA microarrays with genomewide coverage to analyze alveolar macrophages from 15 smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
210
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(229 citation statements)
references
References 55 publications
18
210
0
1
Order By: Relevance
“…OPN concentrations in BALF reflected the find- However, OPN levels in BALF were just above the detection limit of the ELISA system, and therefore have to be interpreted cautiously. Microarray studies already suggested increased OPN expression in smokers, 13,21 but this is the first study showing a clear link between OPN and smoking-related interstitial lung disease.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…OPN concentrations in BALF reflected the find- However, OPN levels in BALF were just above the detection limit of the ELISA system, and therefore have to be interpreted cautiously. Microarray studies already suggested increased OPN expression in smokers, 13,21 but this is the first study showing a clear link between OPN and smoking-related interstitial lung disease.…”
Section: Discussionmentioning
confidence: 78%
“…13,21 Smoking-related interstitial lung diseases are characterized by macrophage accumulation and fibrotic remodeling of the lung. [1][2][3] There is a clear link between cigarette smoke and induction of these diseases, however the responsible substances in cigarette smoke need to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OPN has been identified as a biomarker for various types of cancers and inflammatory diseases (Rangaswami et al, 2006;Ramaiah and Rittling, 2007). Excessive or dysregulated OPN expression has been linked to the pathogenesis of both autoimmune disorders such as multiple sclerosis (Steinman et al, 2002), systemic lupus erythematosus (Zandman-Goddard and Shoenfeld, 2003), rheumatoid arthritis (Xu et al, 2005), atherosclerosis (Ohsuzu, 2004) and other inflammatory diseases including cardiovascular disease , chronic obstructive pulmonary disease (Woodruff et al, 2005), inflammatory bowl disease (Gassler et al, 2002), and asthma (Xanthou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%